Dynamics of vegetation diversity and arbuscular mycorrhizal fungi in post-coal mining revegetation land in Sawahlunto, West Sumatra, Indonesia - WELLY HERMAN; ISKANDAR ISKANDAR; SRI WILARSO BUDI; HERU BAGUS PULUNGGONO; NORIL MILANTARA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Herman W, Iskandar, Budi SW, Pulunggono HB, Kurniati, Milantara N. 2024. Dynamics of vegetation diversity and arbuscular mycorrhizal fungi in post-coal mining revegetation land in Sawahlunto, West Sumatra, Indonesia. Biodiversitas 25: 4627-4641. Post-coal mining causes significant changes in vegetation, soil, and landscape, necessitating reclamation to increase land area through revegetation activities as per government policy. Revegetation is expected to accelerate the recovery of ecosystem functions and reduce the impact of coal mining activities. Therefore, this study aims to analyze the dynamics of vegetation diversity and Arbuscular Mycorrhizal Fungi (AMF) on post-coal mining revegetation land in Sawahlunto, West Sumatra, Indonesia. Vegetation samples were obtained using the purposive sampling method, and AMF analysis was carried out using the wet-sieving decanting method. The results showed an increase in vegetation diversity along with the increasing age of the revegetation plants. The highest control of plant species was Acacia mangium with INP values ??ranging from 100-300%. Vegetation diversity and vegetation dominance index were positively correlated with spore density with correlation coefficient values ??of 0.083 and 0.029. However, the relationship between diversity and vegetation dominance index in influencing spore density had a small effect; the highest spore density was found in revegetation in 2006, with a total of 555 spores per 25 g of soil-1. It can be concluded that natural succession land materials and revegetation in post-coal mining land up to 32 years of age can improve vegetation growth but still cannot match natural forests, both in terms of the number of species growing and the level of vegetation diversity achieved. However, it is important to note that this study has limitations, such as the focus on a specific region and the need for further research to understand the long-term effects of revegetation.